European decorative engravings and the eighteenth-century rococo altarpieces in Trujillo (Peru) - Bailey, Gauvin Alexander (2019)
The impact of rococo has been traditionally overlooked in the retablos of Peru. Although scholars recognized that rococo appeared on certain retablos of late-18th century Lima and Trujillo as decoration, little effort has been made to investigate how the style reached the viceroyalty. This article identifies printed sources from France and Germany (Augsburg) and considers how artists used them. It also compares the treatment of rococo motifs and forms in Trujillo with the way those forms are treated in the Cono Sur (present-day Argentina and Chile). Although the same sources were used in both areas, the retablos of the Cono Sur were frequently made by immigrants (especially from German-speaking lands) while those in the north were usually made by criollo craftsmen.